Advanced processor selection guidance system for optimal computing performance using AHP-profile matching - Winardi, Slamet; Gumelar, Agustinus Bimo; Zulkifli, Che Zalina; Salmanarrizqie, Ageng; Suryo, Philipus (Universitas Trunojoyo Madura, 2025)
The increasing complexity of modern processors and rapid advances in computing technology pose significant challenges for users seeking to select the optimal processor to satisfy their specific requirements. The